Evaluation of Fracture Resistance and Fracture Pattern in Endodontically Treated Maxillary Premolars with MOD Preparation Restored by Direct Composite Onlay and Direct Composite Vonlay - N, Bhavana.; M, Supriya; Ranjith, Ranjith; Pai, Veena (Journal of Neonatal Surgery, 2025)
Aim: To compare the fracture resistance of direct composite vonlays, with intact teeth, full-coverage crowns, and direct composite onlays (2.5 P / 1.5 B cuspal reductions). Materials and Methods: Sixty intact, non-carious human premolars extracted for orthodontic and periodontal reasons were collected. Occlusal stents were prepared for reproducing occlusal anatomy during post endodontic restoration. Standardized MOD cavities were prepared, followed by root canal treatment. Teeth specimens were then prepared for vonlay, onlay, and full crowns. The teeth were divided into four groups (n=15): Group I – Intact teeth; Group II – PFM crowns; Group III – MOD onlay; Group IV – Vonlay. The specimens underwent thermocycling (500 cycles, 5°C to 55°C) and were subjected to fracture testing using a Universal testing machine delivering compressive static loading with a cross head speed of 1mm/min until fracture of the samples. Statistical analysis was done. Mean fracture resistance between different groups was done using Kruskal Wallis Test and Comparison of fracture mode between different study groups was done using Chi Square Test. Results: The mean fracture resistance values were: Group I – 1325.582 ± 71.118 N, Group II – 1026.327 ± 61.561 N, Group III – 788.945 ± 66.388 N, Group IV – 689.561 ± 54.825 N. The differences were statistically significant (P<0.001). Intact teeth showed the highest fracture resistance, followed by PFM, onlay, and vonlay restorations. Fracture mode analysis showed that vonlay restorations had the highest rate of unfavourable fractures. Conclusion: While vonlays had lower fracture resistance than onlays, the difference was not statistically significant. Vonlays may be considered for intermediate restorations in cases with economic and time constraints.